Workshop pengelolaan lahan bekas tambang bagi aparatur pemerintah Nagari Sikabau dan Nagari Tebing Tinggi Kecamatan Pulau Punjung Kabupaten Dharmasraya - Adil Mubarak; Syamsir Syamsir; Aldri Frinaldi (Unri Conference Series: Community Engagement, 2019)
789 hectares of land in Pulau Punjung sub-district are currently in very critical condition, especially in Nagari Sikabau and Nagari Tebing Tinggi. The main cause is the exploitation of natural resources through the activities of the people's gold mining since 2005 which is unstoppable. This situation is exacerbated by the condition of people who do not care and do not have an awareness of the importance of managing environmental sustainability. Nagari government as the spearhead in environmental protection and management is also like losing the idea to initiate a concrete action in dealing with environmental problems in the former mining land. The main cause is the lack of knowledge and skills as well as the capacity of the apparatus in managing the environment on ex-mining land. Through workshops (education and training) with a participatory training approach method will give birth to apparatus who have knowledge, special expertise in the field of environmental management and become a main pillar in building environmentally conscious village communities.